Severe reduction in leukocyte adhesion and monocyte extravasation in mice deficient in CC chemokine receptor 2 - Kuziel, William A. (The National Academy of Sciences of the USA, 1997)
CC chemokine receptor 2 (CCR2) is a prominent receptor for the monocyte chemoattractant protein (MCP) group of CC chemokines. Mice generated by gene targeting to lack CCR2 exhibit normal leukocyte rolling but have a pronounced defect in MCP-1-induced leukocyte firm adhesion to microvascular endothelium and reduced leukocyte extravasation. Constitutive macrophage trafficking into the peritoneal cavity was not significantly different between CCR2-deficient and wild-type mice. However, after intraperitoneal thioglycollate injection, the number of peritoneal macrophages in CCR2-deficient mice did not rise above basal levels, whereas in wild-type mice the number of macrophages at 36 h was ≈3.5 times the basal level. The CCR2-deficient mice showed enhanced early accumulation and delayed clearance of neutrophils and eosinophils. However, by 5 days neutrophils and eosinophils in both CCR2-deficient and wild-type mice had returned to near basal levels, indicating that resolution of this inflammatory response can occur in the absence of macrophage influx and CCR2-mediated activation of the resident peritoneal macrophages. After intravenous injection with yeast β-glucan, wild-type mice formed numerous large, well-defined granulomas throughout the liver parenchyma, whereas CCR2-deficient mice had much fewer and smaller granulomas. These results demonstrate that CCR2 is a major regulator of induced macrophage trafficking in vivo.